The status of HER2 in colorectal carcinoma and the relation of HER2 with prognostic parameters and MSI - Ismail Saygin; Emel Cakir (Wolters Kluwer Medknow Publications, 2022)
Background: Colorectal cancer (CRC) is the third most commonly occurring cancer in men and the second most common cancer in women. Despite advances in surgical techniques and chemotherapeutic regimens, CRC continues to be one of the main causes of cancer-related deaths in the world. Aims: The aim of the study was to evaluate the immunohistochemical expression of human epidermal growth factor receptor 2 (HER2) and the relationship between HER2, clinicopathological parameters, and microsatellite instability (MSI). Materials and Methods: Two hundred and forty resected CRCs at our institution between 2016 and 2019 were included in the study. Tumors were re-evaluated and classified according to the World Health Organization. Tissue macroarray techniques were used to generate tissue samples. HER2 antibody was performed using the automated system. Results: HER2 antibody was score 3 positive in only 5 cases. Score 2 was observed in 13 cases, score 1 in 27, score 0 in 195. All of the HER2-positive cases were metastatic. All of them were tubular adenocarcinoma. HER2 positive cases were well and moderately differentiated. Four of the HER2 positive cases were T3 stage, and one was T4. Conclusion: A total of 2.1% of CRCs were positive for HER2 antibody. There was a positive correlation between HER2 and distant metastasis. There was no significant relationship between MSI, other prognostic parameters, and HER2.